Expert System for Diagnosing Early Childhood Developmental Disorders with Certainty Factor Method - Hermanto, Nandang; Ramadhan, Zulfiqar Shertian (International Journal of Informatics and Information Systems, 2018)
The purpose of this research is to design and build an expert system to diagnose the type of developmental disorder in children early using the certainty factor method. The method of data collection used in this study is observation, interviews, and library studies. The system was built with the Waterfall System Development Method. The stage of the Waterfall method is analysis, design, coding, and testing. This expert system is built using the PHP programming language and MySQL database. The result of this research was to successfully build an expert system to diagnose the type of developmental disorder in children early using the Certainty factor method to facilitate the user in diagnosing developmental disorders in the child quickly, efficiently, and without having to consult a pediatrician.